The Strategic Role of Educational Leaders in Digital Transformation at MAN 1 Banyumas - Aji, Handaru Baskara; Anas, Anas; Ishaac, Muhammad; Sofiana, Arina Nur (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Rapid technological developments in the Industrial Revolution 4.0 and Society 5.0 eras require humans to adapt to change. Technology integration brings significant changes by creating new interactive and meaningful learning experiences, as well as improving the quality of education. The practice of educational institution leadership is very much needed in facing the changing situations and conditions of the development of this era. This study uses a descriptive qualitative method that aims to obtain in-depth findings related to information from sources based on the perceptions, experiences and views of the sources. This research was conducted at Madrasah Aliyah Negeri 1 Banyumas. The objects of this research were the head of the madrasah and several teachers to obtain responses. This study aims to describe the strategic role of educational leaders in digital transformation. The results of the study show that the impact of developments at MAN 1 Banyumas has made the head of the madrasah take strategic steps in integrating technology. The head of the madrasah carries out four strategic roles, namely as an educator, manager, administrator and supervisor. Strategies in adapting to changes and developments in the era include fostering an adaptive mentality, creating innovation and creativity, and optimizing educational resources. The head of the madrasah applies three leadership styles such as participatory, visionary and transformational. Leadership in the era of digital technology has given birth to a new style in collaborating models that can make it easier for madrasah principals to deal with changing situations and conditions when integrating educational technology in madrasahs.